The greatest good for the greatest number of people: an Islamic philosophical analysis - Jalil, Md. Abdul; Mohammed Kamil, Naail; Rahman, Muhammad Khalilur (2013)
The western ethical philosophy provides that if any decision brings the greatest good for the greatest number of people, then the decision is acceptable although a small number of people might be affected by the decision. This is also known as democratic rule of making decision based on majority opinions. There are similar principles in Islam known as ‘al-maslahah al-mursalah’ which means ‘for the public interest’. It means that if any decision is taken by a business leader or by an authority for the interest of public then that decision is acceptable in Islamic jurisprudence. Islam accepts a decision if it is beneficial for the society. There is another principle in Islam which is known as ‘Istihsan’ which means ‘judicial preference’. Muslim scholars use this concept to prefer one decision over another on public interest ground. However, one thing we have to remember that we are the representative (Khalifa) of Allah as well as representative of people. So, whatever decision we make, it should be for the benefit of people and at the same time for the satisfaction of Allah (s.w.t.). The objective of this paper is to critically analyze the possibility of harmonization of the western philosophy ‘the greatest good for the greatest number of people’ with Islamic jurisprudential principles ‘al-maslahah al-mursalah’ and ‘istihsan’. Qualitative research methodology has been applied in this paper.